Experimental Rat and Mouse Carotid Artery Surgery: Injury and Remodeling Studies. (14th May 2013) - Holt, Andrew W.; Tulis, David A.
Abstract : In cardiovascular research, translation of benchtop findings to the whole body environment is often critical in order to gain a more thorough and comprehensive clinical evaluation of the data with direct extrapolation to the human condition. In particular, developmental and/or pathophysiologic vascular growth studies often employ in vitro approaches such as cultured cells or tissue explant models in order to analyze specific cellular, molecular, genetic, and/or biochemical signaling factors under pristine controlled conditions. However, validation of in vitro data in a whole body setting complete with neural, endocrine, and other systemic contributions provides an essential proof of concept from a clinical perspective. Several well-characterized experimental in vivo models exist that provide excellent proof-of-concept tools to examine vascular growth and remodeling in the whole body. This paper will examine the rat carotid artery balloon injury model, the mouse carotid artery wire denudation injury model, and rat and mouse carotid artery ligation models with particular emphasis on minimally invasive surgical access to the site of intervention. Discussion will include key scientific and technical details as well as caveats, limitations, and considerations for the practical use of each of these valuable experimental models.